PEMBERDAYAAN MASYARAKAT PADA DESA WISATA KAMPUNG PATIN DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR TAHUN 2020-2021 - Suryani, Ade Irma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The village has three local village-scale tourist attractions. However, the local community lacks initiative and knowledge for developing tourist attractions in the future. In fact, if this tourist attraction is managed well it will have a positive impact on the community's economy. This research aims to find out the process of tourism-based community empowerment in Koto Mesjid Village. The research method design in this research uses a descriptive qualitative approach that explains systematically, factually and accurately the phenomena raised in this research. The data collection technique uses observation, interviews and documentation. Interviews were conducted with key informants consisting of the Village Head and the implementing team, while supporting informants consisted of members of the Village Community Empowerment (PMD). The data analysis technique involves data reduction and data presentation. The findings in this research show that at the awareness stage in community empowerment, the entire community is included without discriminating against certain classes or groups by capacitating the provision of facilities and infrastructure, counseling and socialization which are held periodically, forming community teams which are divided according to the abilities of each member, realization of performance in the form of mutual cooperation to increase community productivity, however at the community capacity stage it has not been properly capacitated due to the village being unable to fulfill training activities from within. The empowerment stage implements participation, motivation, independent managerial activities, as well as evaluating activities to see community empowerment in management. Keywords: Empowerment, Community, Tourism